A red fluorescent lifeact marker to study actin morphology in podocytes - Eva Wiesner; Julia Binz-Lotter; Simon E. Tröder; David Unnersjö-Jess; Nelli Rutkowski; Branko Zevnik; Bernhard Schermer; Thomas Benzing; Roland Wedlich-Söldner; Matthias J. Hackl (Scientific Reports)
Abstract F-actin is a major component of the cellular cytoskeleton, responsible for maintaining cell shape, enabling movement and facilitating intracellular transport. In the kidney, glomerular podocytes are highly dependent on their actin cytoskeleton shaping their unique foot processes. Hereditary mutations in actin-binding proteins cause focal segmental glomerulosclerosis, while other organs remain largely unaffected. So far, actin visualization in podocytes has been limited to electron microscopy or indirect immunofluorescent labeling of actin-binding proteins. However, the short F-actin-binding peptide Lifeact enables researchers to study actin dynamics in vitro and in vivo with minimal interference with actin metabolism. Here we introduce a new mouse model with conditional expression of a Lifeact.mScarlet-I fusion protein providing red labeling of actin. Cre recombinase-mediated activity allows cell-specific and mosaic expression in podocytes, enabling selective labeling of individual cells to contrast with non-expressing neighboring cells. Transgenic mice are born healthy and young animals display no kidney-related phenotype. By intravital imaging and super-resolution microscopy, we show subcellular localization of actin to the foot processes in a resolution previously only obtainable by electron microscopy. Our novel mouse line provides the opportunity to study the actin cytoskeleton in podocytes and other cell types by intravital imaging and other conventional light microscopy techniques.